Representasi psikologis terhadap kritik sosial dalam karikatur palestina dimedia sosial @osamahajjaj dengan pendekatan sigmund freud - Nariyati, Diah (Maliki Interdisciplinary Journal, 2025)
This study discusses the psychological representation of social criticism through caricatures of Palestine. Using a descriptive qualitative method and Sigmund Freud’s psychoanalytic approach, the research analyzes how visual elements in caricatures represent collective trauma and the lived experiences of the Palestinian people. Caricatures function as a medium to depict the conditions, emotions, and social messages in Palestine, particularly within the context of prolonged conflict. As a tool of social criticism, caricatures reflect public emotions such as fear, suffering, and hope. The methods used include literature review and content analysis of caricatures published on the social media account @osamahajjaj. The findings show that caricatures not only convey social criticism in an easily understandable way but also create space for urgent dialogue. This study emphasizes the importance of understanding the cultural and social context in works of art, as well as how caricatures can serve as reflections of social conditions and as a means of responding to traumatic experiences. These findings are expected to provide new insights for academics, policymakers, and activists in understanding the complex issues in Palestine.